New smokeless moxibustion for knee osteoarthritis: A study protocol for a multicenter, single-blind, randomized controlled trial. Issue 40 (7th October 2022) - Chen, Lusheng; Ren, Xiumei; Li, Fengxing; Deng, Haiping; Ding, Guanghong; Yao, Wei; Zhao, Ling; Shen, Xueyong
Abstract : Introduction: Knee osteoarthritis (KOA) is a chronic inflammatory disease with high morbidity and disability. As the aging and obese population increase, so will the medical services for this disease. The purpose of this study is to compare the clinical efficacy of herbal activated carbon smokeless moxibustion and traditional moxibustion in the treatment of KOA and to determine the clinical efficacy of herbal activated carbon smokeless moxibustion in the treatment of KOA. Methods/design: This is a multicenter, two parallel-group, single-blind, randomized controlled trial. Eighty-eight subjects with KOA (Kellgren Lawrence grade II or III) will be recruited and randomly treated with smokeless moxibustion or traditional moxibustion in the ratio of 1:1. The smokeless moxibustion group will use plant herbal activated carbon smokeless moxa cone. The traditional moxibustion group will be treated with pure moxa cone. Subjects in both groups will receive treatment at the affected knee(s) at the acupuncture point ST35, EX-LE2, and EX-LE4. Subjects in both groups will receive 3 sessions per week of moxibustion for 4 weeks. The primary outcome are changes in the Western Ontario and McMaster Universities Osteoarthritis Index pain scores from baseline to week 24. Secondary outcomes include visual analog scale, 50 yards fast walking time, short-form heath survey 36, overall clinical efficacy evaluation, self-assessment of safety, treatment credibility and expectancy, and cytokines related to osteoarthritis in serum. Discussion: This randomized single-blind controlled trial takes traditional moxibustion as the control group to provide strict evidence for the clinical efficacy and safety of herbal activated carbon smokeless moxibustion in the treatment of KOA.